The efficacy of pain neuroscience education on musculoskeletal pain: A systematic review of the literature - Louw, Adriaan; Zimney, Kory; Puentedura, Emilio J.; Diener, Ina (Physiotherapy theory and practice, 2016)
Objective: Systematic review of randomized control trials (RCTs) for the effectiveness of pain neuroscience education (PNE) on pain, function, disability, psychosocial factors, movement, and healthcare utilization in individuals with chronic musculoskeletal (MSK) pain. Data Sources: Systematic searches were conducted on 11 databases. Secondary searching (PEARLing) was undertaken, whereby reference lists of the selected articles were reviewed for additional references not identified in the primary search. Study Selection: All experimental RCTs evaluating the effect of PNE on chronic MSK pain were considered for inclusion. Additional Limitations: Studies published in English, published within the last 20 years, and patients older than 18 years. No limitations were set on specific outcome measures. Data Extraction: Data were extracted using the participants, interventions, comparison, and outcomes (PICO) approach. Data Synthesis: Study quality of the 13 RCTs used in this review was assessed by 2 reviewers using the PEDro scale. Narrative summary of results is provided for each study in relation to outcomes measurements and effectiveness. Conclusions: Current evidence supports the use of PNE for chronic MSK disorders in reducing pain and improving patient knowledge of pain, improving function and lowering disability, reducing psychosocial factors, enhancing movement, and minimizing healthcare utilization.